Healthy emotions in your child - Rohayah, Husain; Vidya, Bhagat; Mainul, Haque (2019)
Emotional development starts at an early age. This development is significant that it facilitates the children who are in preschool and assist their interaction with others. Indeed, emotional development expedites the overall development of children both in social and intellectual ways. This article aims at conceptualizing developmental mechanisms that promote healthy emotions in children. In a nutshell, views of this article indicate that fostering emotional health in children by using the knowledge about wellness that can shape your healthy life.